تحديات علماء إندونيسيا الكلاسيكيين فى مواجهة التيارات الليبرالية: The Challenges of Indonesian Islamic Classical Scholarly Against Liberal Propaganda - Sempo, Muhammad Widus; Adawiyah, Robiah; Muhammad, Nurzulaili; Fauzi, Nurulwahidah; Ja’far, Nurnajihan; Fasehah, Nurul Asia; Hasyim, Muhyiddin; Najihuddin, Sayyid (‘Abqari Journal, 2019)
Nobody can deny a big role and substantial influence on spreading Islamic education in Indonesia played by Islamic classical scholarly. Coinciding with the spread of liberal propaganda in Muslim society, a liberal group in Indonesia “Jaringan Islam Liberal (JIL)” plans to undermine the societies and Islamic cultures within freedom propaganda and throw away the holistic values of Islam from a daily life of Muslims. Unfortunately, the roles of our Islamic classical scholarly being weakened rather than hundred years ago. They no longer can stop the spread of liberal propaganda. Therefore, this article aims to shed light on the main causes of their weakness to prevent any further spread of liberalism and purify society from its devastating effects. Furthermore, the researchers will point out a better problem solver per issue, using a literature review from a different angle of knowledge. Keywords: challenges, Indonesian, Islamic classical scholarly, liberal ملخص البحث لا أحد يستطيع نفي الظهور المميز لعلماء إندونيسا الكلاسيكيين ودورهم البارز فى نشر تعاليم الإسلام على ربوع أراضى الدولة على مر التاريخ. وتزامنًا مع انتشار الدعاية الليبرالية فى المجتمع الإسلامى التى قام بها فرقة ليبرالية الذين سموا أنفسهم بالتيارات الليبرالية الإسلامية "Jaringan Islam Liberal (JIl)" حيث سعوا إلى تقويض المجتمعات الإسلامية، وإماتة القيم الإسلامية جزئيًا إن لم يكن كليا وإبعادها عن حياة المسلمين، بدت أدوار علماءنا الكلاسيكيين –للأسف الشديد- تضعف فى هذه المرة، وكنا فى أمس الحاجة إليهم للحيلولة دون انتشار الأفكار الليبرالية الهدامة. ولهذا، تهدف هذه الكتابة إلى تسليط الضوء على الأسباب الرئيسة لهذا الضعف والقيام بعلاجها بأفضل ما يتاح لنا من سبيل، وذلك بالرجوع إلى المراجع والمصادر المتاحة من مختلف زوايا المعرفة. الكلمات المفتاحية: تحديات، علماء إندونيسيا، الكلاسيكيين، التيارات الليبرالية